EPISTEMOLOGI PENGEMBANGAN PEMIKIRAN ISLAM MENURUT MUHAMMAD ABID AL-JABIRY - Kandiri Kandiri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
In the presentera ofglobalization,Muslims around the worldautomaticallycome into contact withdifferentcultures anddifferentbeliefs. We often findbothMuslimsas individuals and groupshavedifficulties anduncertaintyin facingglobalizationbecause of becausetheirlack ofpreparation. Scientific building of classicaltheologyis notquite sturdy toprovide a set oftheories andmethodologiesthat may explainhowreligionprovides abenchmark ofscientifictruth(dharuriyah:right and wrong), howknowledgeis produced(hajiyah: good-bad), the goals of science (tahsiniyah:benefit-losses). Axiologicaldimension(whyness) in the scienceof theologyhas a very importantpositionin addition besidesontology(whatness) and epistemology(howness). Islamic lawis oftenchallengedas thecause of theimage, that Islam is anormativeand traditional religion. The slowness, if notstagnation, of theIslamiclaw codification of post-development phase has positioned the backwardness of Islam far behind thedevelopment of human civilizationin general. This studyrevealed thethoughts of Mohammed Abedal-Jabri